A Study On The Impact Of Organization Culture On Job Involvement - et. al., Aanchal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It is a fact acknowledged globally that employees are the greatest asset for any organization. But the real truth behind the said fact is that the biggest asset of any organization is not just "employee" rather its "engaged employee". However, posting right employee in right job within right working atmosphere is the main challenge for any of the organization. Employee participation in the organization is very much dependent on the working atmosphere and the culture of the organization, as every corporation differs in its culture and this may have its own influence on the employee’s involvement in one or the other manner. Employee’s involvement is one of the major factors playing a vital role in achieving Organizational “goal”. The economy growth is also indirectly dependent on employee’s involvement as employees involvement will lead to organization’s growth which contributes to economy of the country. A sense of satisfaction is developed, if the employees finds the workplace to be interactive and as a result of which their involvement in the work will be far better as compared to an organization with a poor working environment and culture.. In this this study, the focus has been centered on understanding the organization culture and its influence on Job Involvement.